2011
DOI: 10.1098/rspb.2010.2657
|View full text |Cite
|
Sign up to set email alerts
|

Kin selection in den sharing develops under limited availability of tree hollows for a forest marsupial

Abstract: Animal social behaviour is not static with regard to environmental change. Flexibility in cooperative resource use may be an important response to resource decline, mediating the impacts of resource availability on fitness and demography. In forest ecosystems, hollow trees are key den resources for many species, but are declining worldwide owing to forestry. Altered patterns of den sharing may mediate the effects of the decline of this resource. We studied den-sharing interactions among hollow-dependent Austra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 49 publications
(109 reference statements)
2
56
0
1
Order By: Relevance
“…Even within the same study region (and species), different studies have revealed contradictory patterns in different populations. Mountain brushtail possums at Cambarville (within the broader region studied here) shared dens less often and used fewer trees where hollow trees were scarce [15], [23], [46]. These results contradict the present findings and are consistent with predictions from theoretical and empirical work suggesting that resource defence behaviour and intolerance of other individuals develops under resource competition [30].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Even within the same study region (and species), different studies have revealed contradictory patterns in different populations. Mountain brushtail possums at Cambarville (within the broader region studied here) shared dens less often and used fewer trees where hollow trees were scarce [15], [23], [46]. These results contradict the present findings and are consistent with predictions from theoretical and empirical work suggesting that resource defence behaviour and intolerance of other individuals develops under resource competition [30].…”
Section: Discussionsupporting
confidence: 68%
“…Commonly, resource-based models of distribution or abundance assume a static relationship between populations and resources [6]. However, increasing evidence demonstrates that the kinds of resources that are used [11], [12], the frequency with which they are used (or avoided) in relation to their availability (the resource selection function) [13], [14], and the degree of resource sharing (cooperation) [15] can vary with resource availability or other changes such as human disturbance or predation pressure [16], [17]. An understanding of the mechanisms by which animals respond to variation in resource availability is essential if we are to predict how resource variation will affect animal populations [9], [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disturbance events may affect social behaviour by mediating the key factors underlying the evolution of social systems, such as demography, genetic population structure and resource availability (Brockhurst et al. 2007, 2010; Banks et al. 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, mountain brushtail possums (Richosurus cunninghami) increased their level of territoriality when their number of dens declined due to habitat destruction (Banks et al 2011), and the availability and distribution of suitable den sites have been suggested to limit group size in Eurasian badgers (Meles meles) (Doncaster & Woodroffe 1993). Aardwolves are primarily nocturnal and dens are important as thermal refugia during periods of inactivity, particularly during the cold dry season when thermal and nutritional stresses are high (Williams et al 1997).…”
mentioning
confidence: 99%